Engineering geological and geotechnical appraisal of Northern Mekelle town, Tigray, Northern Ethiopia - Gure, Ephrem Getahun; Weldearegay, Kifle; Birhane, Gebremedihin (American Scientific Research Journal for Engineering, Technology, and Sciences, 2013)
As population number grows, the demand of constructing buildings for residential, commercial, industrial, and other purposes also increases. Mekelle town is presently rapidly and geometrically expanding towards all directions, and several civil engineering structures such as single to multi-storey buildings, roads, bridges, etc. are under construction. The main research aim is to characterize the engineering geological and geotechnical properties of soils and rocks, and develop detailed multi-purpose engineering geological map at a detail scale. Engineering geological and geotechnical characterization of soils and rocks are based on their index and engineering properties, and their classification is according to the standard proposed by Unified Soil Classification System (USCS) and International association of Engineering Geologists (IAEG (1981). According to USCS; soils are classified into: fat clay type; inorganic silt, elastic silt and (silty of clayey fine sand with slight plasticity) of silt soil types; lean sandy clay, inorganic silts, elastic sandy silt of sandy clay/ silt type; and clayey/ silty sand soil types. According to IAEG (1981); soils are classified into: clay of intermediate and high plasticity; silt of intermediate, high and very high plasticity; SAND clayey of intermediate plasticity, SAND silt of high plasticity; and CLAYEY sand of intermediate, high plasticity and SILT sand of intermediate plasticity). Classification of rock masses is based on their strength, degree of weathering and joint characteristics; classified into three major engineering geological subunits: rocks with low mass strength, rocks with medium mass strength and rocks with high mass strength.